Needs, Comparisons, and Adaptation: The Importance of Relative Income for Life Satisfaction - Wolbring, Tobias; Keuschnigg, Marc; Negele, Eva; et al. (European Sociological Review, 2013)
We examine the association between income and life satisfaction. Referring to the so-called Easterlin paradox, three mechanisms are discussed: basic human need satisfaction, interpersonal comparison processes, and adaptation. Hypotheses resulting from these considerations are empirically tested on the basis of two data sets: a self conducted cross-sectional survey among the population of Munich and GSOEP panel data. In result, all three mechanisms prove of explanatory value. According to our estimates, the threshold for fulfillment of basic needs lies within the range of ∼800 euros disposable income per month in Germany. We also provide weak evidence for social comparison processes concerning the respondents’ city district. More importantly, using a new measurement method for social comparisons, we show life-satisfaction-relevant comparison processes for colleagues and average citizens, but not for friends and relatives. Furthermore, using panel data we confirm hypotheses of aspiration and adaptation. Thus, relative income (social as well as temporal) is more important for life satisfaction than absolute income. Moreover, as theoretically expected, income losses have a stronger influence on life satisfaction than income gains—a finding which can also be transferred to social comparisons..